Vertebral arteries: A target for FDGPET imaging in giant cell arteritis? - Pfadenhauer, K.; Weinerth, J.; Hrdina, C. (Nuklearmedizin - NuclearMedicine, 2011)
Aim: To demonstrate the capacity of FDG-PET to show active giant cell arteritis (GCA) of the extracerebral vertebral artery (VA) and to compare it with clinical, ultrasonographic (US) and biopsy findings. Patients, methods: Observational study of 46 consecutive patients with the diagnosis of active GCA and abnormal high FDG uptake in the aorta and other large arteries suggestive for GCA. Results: 15 of the 46 GCA patients had abnormal high FDG uptake within the extending from the V0 to V3 segment in 13 and confined to single segments in 2 patients. In 2 patients high FDG uptake in one VA was the onIy PET abnormality. In 13 patients high FDG uptake was also found in other large arteries (carotid n = 10, subclavian/axillary artery n = 12, thoracic aorta n = 12). Abnormal PET was detectable in 5 patients despite glucocorticoid (GC) treatment. Nuchal and occipital pain and ischemic stroke or TIA in the posterior circulation (n = 3) were found in 10 patients with high VA FDG uptake. US detected halos of the V0–2 segments in 8/46 patients (5/15 VA PET positive and 3/31 VA PET negative patients). Biopsies were available in 10/15 VA PET positive patients with evidence of active GCA in 7 cases. Conclusion: In patients with severe GCA and a high TVS the extracranial VA are a good target for PET imaging in active GCA with abnormal findings in 33% of patients with a positive PET. VA abnormalities can be an early and isolated finding in active GCA. PET is superior to US for the detection of active VA-GCA. A strong correlation between VA abnormalities and associated clinical abnormalities existed in 2/3 of patients. PET abnormalities of the VA could be detected in some cases after GC treatment has been started even at high doses.
Keywords: FDG-PET; vertebral arteries; giant cell arteritis